(untitled) (Lundiana: International Journal of Biodiversity, 2016)
Frogs from the Family Leptodactylidae are among the most important opportunistic feeders on other anuran species. Here we report a case of predation of Pseudis platensis by the Cei’s white-lipped frog Leptodactylus chaquensis in breeding habitat from agricultural landscape, southern Brazil.